INTEGRATED LEARNING IN THE MATHEMATICS AND NATURAL SCIENCES LEARNING PROCESS IN HIGH SCHOOL - Reihenova, Austra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article discusses the integrated process of learning mathematics at secondary school. The content of teaching mathematics must be arranged in such a way that the student develops an overall understanding of the world. The aim of the article is to emphasize the depth of comprehension of the content of the subject of the student’s interest, because based on the understanding of the content of the subject, new knowledge will be integrated and new skills will be developed that the student will be able to transfer to other subjects by solving problem situations. The topicality of the article is related to the integration approach, that the main focus is not to focus on the content of the subjects of mathematics and physics, but on the scientific processes that unite the contents of these subjects. Theoretical basis of the research is the system theory, which is based on the approach of learning cognition and constructivism. In the research, students' complex tests and questionnaires with open questions were used for data acquisition. The article uses a case study design to analyse data.